2020
DOI: 10.1016/j.jeap.2020.100846
|View full text |Cite
|
Sign up to set email alerts
|

The provision of student support on English Medium Instruction programmes in Japan and China

Abstract: This is an author generated .pdf for a journal article (Galloway, N. and Ruegg, R (2020). The provision of student support on English Medium Instruction programmes in Japan and China . EAP Journal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
74
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(87 citation statements)
references
References 24 publications
12
74
1
Order By: Relevance
“…The issues encountered by EMI lecturers were also evidenced in Simbolon's (2017) study. The challenges mentioned above are suggested to link with the fact that there is no consensus between the understandings of stakeholders and EMI implementation (Galloway & Ruegg, 2020;Aizawa & Rose, 2018;Simbolon, 2018). This inconsistency seems to cause institutions' limited support to both teachers and students and teachers to their students in EMI classrooms.…”
Section: Previous Studies On Emimentioning
confidence: 99%
See 1 more Smart Citation
“…The issues encountered by EMI lecturers were also evidenced in Simbolon's (2017) study. The challenges mentioned above are suggested to link with the fact that there is no consensus between the understandings of stakeholders and EMI implementation (Galloway & Ruegg, 2020;Aizawa & Rose, 2018;Simbolon, 2018). This inconsistency seems to cause institutions' limited support to both teachers and students and teachers to their students in EMI classrooms.…”
Section: Previous Studies On Emimentioning
confidence: 99%
“…However, research on documenting EMI practice in Indonesia is in a stage of infancy because HE institutions' internationalization process commenced only about a decade ago (Simbolon, 2018). In global contexts, studies on EMI issues show a somewhat broad gap between the expectation of the benefits of EMI and its actual-ideal implementation (Dearden, 2015;Galloway & Ruegg, 2020;Simbolon, 2018;Simbolon, Oliver, & Mercieca, 2020). The study reported in this article was done to shed light on the current practice of EMI in Indonesian universities by examining their strategies in obtaining international recognition.…”
Section: Introductionmentioning
confidence: 99%
“…It is widely regarded as a medium of instruction in non-English regions of the world [10]. Dr. Nicola Galloway [19] cited practical reasons for the spread of EMI after carrying out a study of EMI students in Japan and China. Most academic research is published in English (about 94 per cent of research in international, high-impact publications is in English).…”
Section: Issues Of Introducing Emi As a Powerful Tool For Interdiscipmentioning
confidence: 99%
“…She also praised "the booming Chinese English language teaching industry. Although the incorporation of English Medium Instruction (EMI) in multilingual higher education institutions is widely accepted [10,19,20], according to Joan Catherine Ploettner, having conducted a study of EMI students in Spain and Portugal, "it may be a source of tension for university professors for whom English is an additional language, particularly when both teacher and students share an L1 other than English." As practice shows, EMI has not yet been widely applied in the practice of non-linguistic universities in general and especially in peripheral technical universities with a small contingent of students.…”
Section: Issues Of Introducing Emi As a Powerful Tool For Interdiscipmentioning
confidence: 99%
See 1 more Smart Citation